The Role of Vocabulary and Grammar in Indonesian Language Learning at Schools - Masitoh, Siti; Teja Pratama , Rizki; Aryana, Suhud; Ardiansyah (JLER (Journal of Language Education Research), 2025)
This study began with the discovery of problems in language learners who often forget the role of acquiring newvocabulary and the application of grammar in its use. The purpose of this study was to determine the Indonesian languagelearning methodology in aspects of acquiring new vocabulary at school and learning grammar in schools. This research method uses the literature study method. The results of this study obtained various kinds of vocabulary and grammarlearning strategies that are suitable to be applied in schools based on their respective roles. The learning strategies are divided into two, namely strategies for vocabulary and strategies for grammar. Vocabulary includes (1) Word list strategy and frequency count (2) Vocabulary and context (3) Vocabulary development and second language acquisition (4)Introducing prepositions and pronouns (5) Channell's strategy compares research into speech errors of native speakers with second language learners (6) Semantic networks and features (7) Memory and vocabulary development (8) Comprehension and product techniques. Meanwhile, the learning of grammar includes (1) traditional language classes (2)The acquisition of a second language and its effect on practice (3) Pedagogical materials and techniques for teaching grammar.